Austerity, path dependency and the (re)configuration of policing - Topping, John (Policing and society, 2022)
As a standard operating backdrop in the United Kingdom, for more than a decade austerity has become an increasingly dominant logic as to how policing can be delivered and (re)configured to do ‘more with less’. Yet beyond simple rationalisation of public policing in line with market principles, a more complex and long-standing trajectory underpins relations between the police and commercial ‘others’ set within this climate. With austerity as a guiding ‘code’, it has accelerated rather than punctuated the evolution of public policing dispersal. Using path dependency theory, the paper argues that change across both law and policy via different forms of critical juncture has embedded commercial principles, while simultaneously reconfiguring the symbolic (and operational) status of the police and their relationship with the public. In turn, the paper highlights that such pluralisation, in a genealogical sense, has tilted police authority away from central state control to a more dispersed and commercial model – but on a long-term trajectory which long precedes austerity as part of path-dependent change.